ANALISIS USULAN KEBIJAKAN SOLUSI KEMACETAN LALU-LINTAS DI KAWASAN TEMBALANG SEMARANG - Arum Septiana; Mulyo Hendarto (Universitas Diponegoro, 2012)
ABSTRACT This study aims to describe about traffic congestion on Prof. Soedarto street in Tembalang area, Semarang and to analyze an its policy. In 2010, happens moved University Diponegoro student from Pleburan to Tembalang area. It’s caused Tembalang area become crowded. This research used Analitical Hirarchy Process (AHP) method. The analysis applied against ten variable of traffic congestion policy that the result derived from interview and discussion with key informans. The result of this research that entire respondent chosen the policy proposal make the new road as solution to overcome the traffic congestion.